Vrae na die sin van die werklikheid met verwysing na die Agogiese - Schoeman, P. G. (Koers, 1989)
Questions about reality with special reference to the agogical. Reflection on the meaning of reality and man's existence is peculiar to human beings and virtually as old as man himself. This problem has been addressed in the works of philosophers through the ages, and was brought to a head during the twentieth century by exponents of the extentialist philosophy. It is also of relevance for the education is t. This article is an attempt to elucidate this problem and its bearing on education against the background of the Scriptural basic motive of creation, fall and redemption and the Christian cosmonomic idea which is the transcendental basic idea of reformational philosophy.